Crystallographic aspect of shear bands formation in pure iron deformed at high strain rates. Issue 1 (1st December 2022) - Mania, I; Paul, H; Chulist, R; Petrzak, P; Prażmowski, M
Abstract : In this paper results on shear bands developed in pure iron are presented. The main focus was put on microstructural characterization and crystal lattice rotation in sheared regions. The hat-shaped samples were deformed at a high strain rate of 560 s −1 using a drop-hammer. The microstructure of deformed specimen was investigated by optical microscopy and scanning electron microscopy equipped with a high-resolution electron backscattered diffraction facility. The changes of mechanical properties in the band area and neighbouring matrix were investigated using nano-indentation test. This paper clearly shows that initial stages of shear bands formation are associated with the formation of kink-type bands. The orientation maps revealed the crystallographic determination of the shear band formation. During deformation in each grain located within the sheared region, one of the {110}-type planes situate along the macro-shear band plane and <111> direction situates along the shear direction. In consequence, the formation of specific texture components within the shear band region was observed, different from texture observed in deformed matrix. In micro-scale no effects of dynamic recrystallization were observed. Nano-hardness tests indicated that notable increase of strain hardening is related to the strain localization in narrow shear band' regions, while the matrix undergoes almost no deformation.